Psychosocial functioning of adolescents with ADHD in the family, school and peer group: A scoping review protocol. - Kinga Karteczka-Świętek; Sylwia Opozda-Suder; Agnieszka Strojny (PLoS ONE)
Objective The objective of this scoping review is to investigate what is known about the psychosocial functioning of adolescents with ADHD. All basic life environments (family, school and peer group) will be considered. Introduction Adolescence is especially critical for people with ADHD-natural maturation may be accompanied by changing symptoms of ADHD. A number of childhood difficulties transform during adolescence and contribute to problems in various areas that comprise psychosocial functioning. The available studies focus on selected domains of psychosocial functioning of adolescents with ADHD, however, to the authors' best knowledge, there is no comprehensive description of this issue. The lack of such a description is the main rationale for conducting this scoping review. Inclusion criteria Pointing to the PCC elements (population, concept, context), the scoping review will include primary studies on the concept of psychosocial functioning (including functioning in the family, school and peer group). In the included studies, the term "psychosocial functioning" (or related) had to be used explicitly. The population will be adolescents (10 to 19 years old) with a formal diagnosis of ADHD (DSM classification) or Hyperkinetic Syndrome (ICD-9) or Hyperkinetic Disorders (ICD-10). There will be no restrictions on the research context. Methods The methodology of scoping reviews will be applied in accordance with the guidelines of the Joanna Briggs Institute (JBI). The following databases: Academic Search Ultimate, ERIC, MEDLINE, ProQuest Central, PsycInfo, Scopus, and databases under the Web of Science will be searched for primary studies in peer-reviewed journals, written in English and published since 1987. The analyses will be based mainly on frequency counts of the components of psychosocial functioning and population characteristics. The results will be presented in tabular form and supplemented with a descriptive summary. The protocol has been registered on the Open Science Framework: https://doi.org/10.17605/OSF.IO/MS82H [registration DOI].